Determination of the Amount of Instant Noodle Production By Applying the Fuzzy Mamdani Method at PT. Indofood CBP Sukses Makmur Tbk Medan - Jon Parlagutan Panjaitan (Institute of Computer Science, 2020)
The problem that often occurs in a company is difficult to determine the amount of production that must be produced, this is because the number of requests is not always fixed or there is no certainty. So also at PT Indofood CBP Sukses Makmur Tbk Medan which is engaged in the production of instant noodles. Fuzzy logic is one method for analyzing systems that contain uncertainty. The author uses the method mamdani or often also known method Min - Max, in this study the author uses data on the number of requests and the amount of inventory in PT. Indofood CBP prosperous success in the field from January to March 2018. System design to get output is done in stages (a) formation of fuzzy sets. (b) application of implication functions, (c) forming rules, (d) confirmation (defuzzification). In this study defuzzification is done using the centroid method